State-of-the-Art and Energy Management System of Lithium-Ion Batteries in Electric Vehicle Applications: Issues and Recommendations - Hannan M.A.; Hoque M.M.; Hussain A.; Yusof Y.; Ker P.J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Anodes; Battery management systems; Battery storage; Cathodes; Condition monitoring; Cost reduction; Electric batteries; Electric discharges; Electric vehicles; Electrodes; Electrolytes; Electronic Waste; Energy management; Energy management systems; Environmental impact; Environmental technology; Fault detection; Greenhouse gases; International trade; Ions; Lithium; Recycling; Secondary batteries; Vehicles; Advanced lithium-ion batteries; Battery manufacturing; Charge and discharge; Electric Vehicles (EVs); In-vehicle applications; Performance evaluations; State of the art; Vehicle applications; Lithium-ion batteries